Milk protein suspensions enriched with three essential minerals: Physicochemical characterization and aggregation induced by a novel enzymatic pool - Lombardi, Julia (2015)
Structural changes of casein micelles and their aggregation induced by a novel enzymatic pool isolated from Bacillus spp. in the presence of calcium, magnesium or zinc were investigated. The effect of cations on milk protein structure was studied using fluorescence and dynamic light scattering. In the presence of cations, milk protein structure rearrangements and larger casein micelle size were observed. The interaction of milk proteins with zinc appears to be of a different nature than that with calcium or magnesium. Under the experimental conditions assayed, the affinity of each cation for some groups present in milk proteins seems to play an important role, besides electrostatic interaction. On the other hand, the lowest aggregation times were achieved at the highest calcium and zinc concentrations (15 mM and 0.25 mM, respectively). The study found that the faster the aggregation of casein micelles, the less compact the gel matrix obtained. Cation concentrations affected milk protein aggregation kinetics and the structure of the aggregates formed.